William Gibson and the Future of Contemporary Culture - Nilges, Mathias; Murray, Mitch R. (Book collections on Project MUSE., 2020)
"William Gibson is frequently described as one of the most influential writers of the past few decades, yet his oeuvre has only been studied partially and without full recognition of its implications for literature and culture beyond science fiction. It is high time, then, for a book that explores the significance and wide-ranging impact of Gibson's fiction. This book brings together emerging and established literary critics and exciting new voices in contemporary science fiction to discuss the importance of Gibson's work for recent literary and cultural history. In the 1970s and 80s, Gibson, the "Godfather of Cyberpunk," rejuvenated science fiction. In groundbreaking works such as Neuromancer (1984) that changed SF as we knew it, Gibson provided us with a language and imaginary through which it became possible to make sense of the newly emerging world of globalization and the digital and media age. Ever since, Gibson's reformulation of SF has provided us with not just with radically innovative visions of the future but indeed with trenchant analyses of our historical present and of the emergence and exhaustion of possible futures. The essays collected in this book therefore not only trace the influence of Gibson's work on literature and culture over the past four decades, but they also illustrate how Gibson's work helps us understand the historical development of recent culture, such as the transition from the rise of cyberpunk to the new forms of realism that determine literary culture of the 2000s and toward a new turn to SF in the context of the crises of futurity that define the contemporary moment. Understanding Gibson, this book shows, allows us to understand some of the most fundamental historical developments of recent literature and culture, and it thereby offers us new ways of interrogating and understanding our own time"--